COVID-19 with Acute Cholecystitis: A Case Report - Syam, Ari Fahrial; Achmadsyah, Armand; Mazni, Yarman; Sari, Cut Yulia Indah (The Indonesian Society for Digestive Endoscopy, 2022)
Novel Coronavirus 2019 (COVID-19) also known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is an enveloped, non-segmented positive-sense RNA virus that belonging to the beta-coronaviridae family. Patients were said to had various symptoms of fever, cough, anosmia, and chest stuffiness in addition to other non-specific clinical manifestations, including diarrhea, vomiting, anorexia, abdominal pain, and so on. Although this gastrointestinal symptoms were present in COVID-19 case, there was not enough evidence about the involvement of gallbladder and biliary tract in literature to date. We report a rare case of Acute Cholecystitis on a COVID-19 patient in Jakarta, Indonesia. A case of 54-year-old female with COVID-19 confirmed by RT-PCR Test who had constant pain in the right upper quadrant of her abdomen during her arrival at the hospital that was finally diagnosed as Acute Cholecystitis. The Laboratory Findings revealed normal level of White Blood Cells(6.73 K/aeL). The Multidisciplinary team decided to treat COVID-19 infection with antiviral (Favipiravir, according to Indonesian COVID-19 Guideline) for 2 weeks until her RT-PCR was found to be negative then perform a laparoscopic cholecystectomy as the first treatment. During the administration of Favipiravir, there was a reduction of pain in the right upper quadrant abdomen and an overall clinical improvement.The precise mechanism of Acute Cholecystitis in COVID-19 Patients was still unclear. However, Acute Cholecystitis could be a possible complication of COVID-19 although there was not enough evidence whether the gallbladder might be vulnerable to COVID-19. In this case, the normal level of white blood cells could be a hint that Acute Cholecystitis was not caused by bacterial colonization and could be potentially triggered by COVID-19. Laparoscopic Cholecystectomy was chosen as the first management after RT-PCR COVID-19 was negative with 2-weeks of antiviral treatment. Although the lack of evidence and guidelines for Acute Cholecystitis management during The COVID-19 Pandemic, Laparoscopic Cholecystectomy remains the chosen treatment for Acute Cholecystitis Management on COVID-19 Patients. More research is needed to understand the possible relationship between Acute Cholecystitis and COVID-19.